Pharmaceutical and drug delivery applications of pectin and its modified nanocomposites - Welela Meka Kedir; Ebisa Mirete Deresa; Tamiru Fayisa Diriba (Heliyon, 2022)
Due to their natural availability, biocompatibility, biodegradability, nontoxicity, flexibility, as well as improved structural and functional characteristics, pectin and pectin-based nanocomposites have become an interesting area of numerous researchers. Pectin is a polysaccharide that comes from plants and is used in a variety of products. The significance of pectin polysaccharide and its modified nanocomposites in a number of applications has been shown in numerous reviews. On their uses in pharmaceutical and medication delivery, there are, however, few review publications. The majority of papers on pectin polysaccharide do not structure their explanations of drug distribution and medicinal application. The biological application of pectin nanocomposite is also explained in this review, along with a recent publication. As a result, the goal of this review was in-depth analysis to summarize biological application of pectin and its modified nanocomposites. Due to their exceptional physicochemical and biological characteristics, pectin and its nanocomposites are remarkable materials for medicinal applications. In addition to enhancing the immune system, controlling blood cholesterol, and other things, they have been shown to have anticancer, antidiabetic, antioxidant, anti-inflammatory, immunomodulatory, and antibacterial properties. Because of their biocompatibility and properties that allow for regulated release, they have also received a lot of interest as drug carriers in targeted drug delivery systems. They have been used to administer medications to treat cancer, inflammation, pain, Alzheimer's, bacteria, and relax muscles. This review found that pectin and its derivatives have better drug delivery efficiency and are viable candidates for a wide range of medicinal applications. It has been advised to conduct further research on the subject of toxicity in order to produce commercial formulations that can serve as both therapeutic agents and drug carriers.